A COMPARISON BETWEEN WATER RELATED STRATEGIES – LEADING TO A PROPOSED ROMANIAN WATER SECURITY STRATEGY - MASTAN, Raul-Adrian; ROȘU, Cristina (Studia Universitatis Babeș-Bolyai Ambientum, 2024)
This article makes a comparative analysis between the National Strategy for Water Management in Romania draft (which is in the final steps of being approved), the Someș Water Company (CAS) master plan, the Romanian national management plan related to the Danube’s River basin portion in Romania and the strategies of the authorities from England and those from the USA, which have a focus on water security. A comparison between the different paradigms of these 5 parties will be made, that will represent the basis of the author’s proposal for an alternative National Water Security Strategy in Romania. At the end, the necessary recommendations will be made for the development of such a strategy as well as other recommendations in case it will not be developed.